The effect of withholding salt on the growth and condition of steers, 1951-52. - Smith, E.F.; Parrish, D.B.; Splitter, E.J. (Kansas Agricultural Experiment Station, 2012)
Twenty head of good quality Hereford steer calves were used in the test. They were a part of the heavy end of a group of 150 calves purchased in the vicinity of Marfa, Texas, for experimental tests. There are two lots, 10 head to a lot, and both lots are being self-fed a ground milo grain and chopped alfalfa hay mixture at the rate of 3 pounds of milo grain to 1 pound of alfalfa hay. Lot 1 has free access to salt, whereas salt is being withheld from Lot 2.
Keywords: Beef; Salt; Ground milo; Alfalfa hay